The Comparative Estimation of Primary Students’ Programming Outcomes Based on Traditional and Distance Out-of-School Extracurricular Informatics Education in Electronics Courses during the Challenging COVID-19 Period - Taras Panskyi (MDPI AG, 2021)
The authors decided to investigate the impact of the lockdown period and the resulting limitations in informatics education, especially programming, in out-of-school electronics courses using traditional and distance learning modes in primary school COVID-19 pandemic settings. Two extracurricular courses were held successively; the first electronics course was performed in a traditional out-of-school learning mode using Arduino kits, while the other was held using the TinkerCad circuits virtual environment in distance learning mode. A structured questionnaire was administered to students to map their knowledge of programming. The questionnaire consists of three emotional dimensions: enjoyment, satisfaction and motivation. The fourth dimension was dedicated to the students’ programming outcomes. Three emotional dimensions were addressed to primary school students, while the fourth dimension was addressed to the tutors’ observations toward the students’ programming outcomes. The obtained results revealed that learning modes have no significant impact on students perceiving the programming issues. However, three emotional dimensions revealed a significant difference in the students’ enjoyment, satisfaction and motivation in favor of the traditional learning mode. Our findings are of particular interest in light of possible crisis-prompted distance education in the future but can also serve to inform government institutions and policymakers seeking to develop effective concepts for successful distance learning.